Lexicostatistics Study of Mandailing and Angkola Languages - Harianto II Harianto II; Zulfitri Zulfitri; Teguh Satria Amin (Universitas Majalengka, 2021)
This research was conducted to discuss the relationship between the Mandailing and Angkola languages by studying the lexicostatistics side to discuss the degree of kinship of the two regional languages in North Sumatra. This research makes comparisons based on 200 Morris Swadesh vocabulary which is the main reference in research and studying the relationship between the Mandailing language and the Angkola language. The purpose of this study was to determine the percentage of kinship between the Mandailing and Angkola languages in North Sumatra. Then determine the time of separation between the two languages with the study of the lexicostatistics. And also explains the sound correspondence between the Mandailing and Angkola languages. The research method used in this study is a qualitative method and also a quantitative method. From the results of this study it was explained that the Mandailing and Angkola languages have a fairly close kinship side. Especially if you look at the similarity comparison of the number of words consisting of 98 words. Then the sound correspondence itself consists of, 1) replacement of sounds or phonemes consisting of 10 words, 2) reduction of sounds or phonemes with a total of about 16 words and also 3) addition of sounds or phonemes with a total of 18 words. The kinship relationship that occurs between the Mandailing and Angkola languages accounts for around 71% of the 200 Glossary of Morris Swadesh's vocabulary obtained from the two languages. The year of separation of these two languages, namely Mandailing and Angkola, was around 1,235 years ago, starting from 2023. The two languages are in the same sub-family and are in the same family.